Comparison of Compression Performance and Energy Absorption of Lattice Structures Fabricated by Selective Laser Melting - Shi, Xin; Liao, Wenhe; Li, Peifeng; Zhang, Changdong; Liu, Tingting; Wang, Cong; Wu, Jiajing (Advanced engineering materials, 2020)
Selective laser melting (SLM) enables the fabrication of highly complex lattice structures, such as a novel triply periodic minimal surface (TPMS) lattice structure. This article investigates the compression performance and energy absorption capacity of four SLM TPMS lattice structures with Gyroid, Diamond, IW, and Primitive unit cells. The deformation and failure modes are analyzed by both the mechanical experiments and finite‐element simulation. The compression performance and energy absorption of Gyroid and IW structures with different relative densities are also researched. The results show that the deformation mode is bending‐torsional coupling dominated in Gyroid, Diamond, and IW structures. IW and Gyroid structures have higher compression performance and energy absorption. However, Primitive structures have highest compression performance and lowest energy absorption for its stretch‐dominated deformation mode. The compressive strength and modulus of Gyroid and IW structures can be related to the relative density by the Gibson–Ashby model. With the relative densities of 4.6–8.6%, the Gyroid structure has higher energy absorption. However, the IW structure has higher energy absorption with the relative densities of 8.6–12.6%. Herein, compression performance and energy absorption of four selective laser melting (SLM) triply periodic minimal surface (TPMS) lattice structures with Gyroid, Diamond, IW, and Primitive unit cells are investigated. The deformation modes are analyzed by experiments and finite‐element simulation. Finally, compression performance and energy absorption of Gyroid and IW structures with different relative densities are also compared.